Development of Low-Fat Mayonnaise with Natural Colorant from Tomato Peels Nanopowder - Evanuarini, Herly; Agus Susilo; Dedes Amertaningtyas (Jurnal Ilmu-Ilmu Peternakan, 2023)
Tomato peel is an industrial waste product from tomato vegetables that has not been utilized properly. Industrial waste that has not been utilized will harm the environment. Tomato peel is a source of natural food coloring, antioxidants, and a source of fiber. Application of tomato peel can be added to mayonnaise products to improve the color of low-fat mayonnaise. This study aimed to investigate the effect of giving tomato peel nanopowder as a natural coloring in low-fat mayonnaise based on pH, total acid, protein content, carbohydrates, color, and sensory quality. Low-fat mayonnaise was prepared using sunflower oil, vinegar, and egg yolks by giving the tomato peel nanopowder treatment of 0, 1, 2, and 3% which was repeated 5 times. Analysis of variance (ANOVA) was used as data analysis if there were differences in effect between the treatments, followed by Duncan's Multiple Range Test (DMRT). The research results of adding tomato peel nanopowder with different percentages had a very significant effect (p<0.01) on pH, total acid, protein content, carbohydrates, color, and sensory quality. This research concludes that 3% tomato peel nanopowder applied to low-fat mayonnaise can improve pH, total acid, protein content, carbohydrate, L, a*, b*, and sensory quality.